Analisis Karakter Mahasiswa dalam Berwirausaha - Lussyana Karolina Sidebang; Sheryl Valencia Pangaribuan; Fitri Novi Yanti Munthe; Putri Kemala Dewi Lubis (Economic Reviews Journal, 2024)
This research uses a qualitative approach with in-depth interviews with a number of entrepreneurial students to understand their creative and innovative characteristics in their business. Analysis shows that students who are creative and innovative tend to have a risk-taking attitude, flexibility in facing change, and the ability to identify new market opportunities. They also tend to have a strong intrinsic motivation to create value for consumers. Students’ creative and innovative character plays an important role in the success of their business. Education and institutional support can strengthen these traits, encouraging students to become leaders in their entrepreneurial fields. To increase support for students’ creative and innovative characteristics, institutions need to provide educational programs that focus on developing new ideas, as well as providing access to financial resources and mentorship for young entrepreneurs. Analysis of students’ creative and innovative characteristics provides important insights into how young people can contribute significantly to the economy through their own businesses.